Toxicokinetic Modeling Challenges for Aquatic Nanotoxicology - Chen, Wei-Yu (Frontiers in Marine Science, 2016)
Nanotoxicity has become of increasing concern since the rapid development of metal nanoparticles (NPs). Aquatic nanotoxicity depends on crucial qualitative and quantitative properties of nanomaterials that induce adverse effects on subcellular, tissue, and organ level. The dose-response effects of size-dependent metal NPs, however, are not well investigated in aquatic organisms. In order to determine the uptake and elimination rate constants for metal NPs in the metabolically active/ detoxified pool of tissues, a one-compartmental toxicokinetic model can be applied when subcellular partitioning of metal NPs data would be available. The present review is an attempt to describe the nano-characteristics of toxicokinetics and subcellular partitioning on aquatic organisms with the help of the mechanistic modeling for NP size-dependent physiochemical properties and parameters. Physiologically-based pharmacokinetic (PBPK) models can provide an effective tool to estimate the time course of NP accumulation in target organs and is useful in quantitative risk assessments. NP accumulation in fish should take into account different effects of different NP sizes to better understand tissue accumulative capacities and dynamics. The size-dependent NP partition coefficient is a crucial parameter that influences tissue accumulation levels in PBPK modeling. Further research is needed to construct the effective systems-level oriented toxicokinetic model that can provide a useful tool to develop quantitatively the robustly approximate relations that convey a better insight into the impacts of environmental metal NPs on subcellular and tissue/organ responses in aquatic organisms.